User generated content sebagai strategi komunikasi pemasaran digital: studi kasus fenomena #shopeehaul - Nisrina, Rumaysha Gikha (Jurnal Komunikasi Profesional, 2021)
The dynamic development of communication technology certainly brings changes in various aspects including marketing. The presence of digital channels brings new access for companies or brands to convey their marketing messages. The difference between analogue and digital marketing, of course, results in different marketing strategies. Changes in the orientation of the product to consumers also have an effect. In digital marketing, user generated content is an important feature, especially with the increasing number of social media users, including in Indonesia. As in the case of the '#Shopee Haul’ phenomenon, where user generated content becomes a digital marketing strategy that has a positive impact on product sales. This research focuses on how user generated content can be an effective digital marketing strategy from a user perspective, using descriptive qualitative methods and case studies. Primary data sources were obtained from interviews with informants who met the criteria (purposive sampling), and were supported by secondary data sources derived from participatory observation. As a result, user generated content can be an effective digital strategy due to the features attached to UGC itself, such as personal values and individual creativity, motivation to share information and social benefits.